Glutamate-associated research in Parkinson’s disease: a bibliometric analysis - Chen, Yan-Jun; Xie, Ming-Rong; Zhou, Sheng-Qiang; Liu, Fang (Frontiers in Aging Neuroscience, 2025)
BackgroundParkinson’s disease (PD) is a common neurodegenerative disease. As an important excitatory neurotransmitter, glutamate plays a key role in the nervous system. The imbalance of glutamate levels, the dysfunction of related receptors, and the abnormal activity of transporters are closely associated with the pathological process of PD. This study aims to explore the research hotspots, frontiers, and development directions of PD and glutamate.MethodThe relevant publications were obtained from the Web of Science. CiteSpace, VOSviewer, and bibliometrix were used for visualization and quantitative evaluation.ResultsA total of 2,488 publications related to the research topic were included. From 2001 to 2024, the annual number of publications showed a fluctuating upward trend. The United States was a leader in this field, working closely with China, Italy, the United Kingdom, and France. Karolinska Institute was the most active institution. Core journals were mainly related to neuroscience, covering basic research, clinical applications, and pharmacology. Dr. Conn, P. Jeffrey was the most productive author. The paper “The functional anatomy of basal ganglia disorders” was the most co-cited literature. High-frequency keywords included PD, glutamate, basal ganglia, oxidative stress, dopamine (DA), neurons, alpha-synuclein (a-Syn), glutamate receptors, and synaptic plasticity. In recent years, a-Syn and neuroinflammation were the research topics with strong burst power.ConclusionResearch on PD and glutamate focused on countries with increasing aging. The collaboration of different countries and institutions was conducive to promoting the development of this field. The research hotspots included basal ganglia, oxidative stress, DA, neurons, a-Syn, glutamate receptors, and synaptic plasticity. a-Syn and neuroinflammation may be research directions in the future.